Personally tax aggressive executives and corporate tax sheltering - Chyz, James A. (Journal of Accounting and Economics, 2013)
This paper investigates whether executives who evidence a propensity for personal tax evasion (suspect executives) are associated with tax sheltering at the firm level. I adapt recent research to identify the presence of these executives and examine associations between suspect executive presence and firm-level measures of tax sheltering. The results indicate that the presence of suspect executives is positively associated with proxies for corporate tax sheltering. In addition, firm-years with suspect executive presence have significantly higher cash tax savings relative to firm-years without suspect executive presence. I also investigate the firm value implications of suspect executive presence and find that increases in tax sheltering are incrementally more valuable for firms that have suspect executives than similar increments made by firms that do not have suspect executives.